"The witch. She is in her house"--"We don't have witches here. Not in Soweto": Soweto witchcraft accusations in the transition from apartheid through liberation to democracy - Wardrop, Joan (DOBU Verlag, 2007)
During 1994 and 1995 major-crime emergency response police (Soweto Flying Squad) in the largest black township in South Africa noticed and frequently discussed a rise in the number of witchcraft-related complaints, incidents and requests for assistance. In that time of transition and deep cultural anxiety, the atmosphere in Soweto was often seething with resentments and concerns which had been suppressed during the apartheid years of oppression but which now bubbled to the surface in often unexpected ways, exemplified in the two contradictory statements in this paper's title, each made by a middle-aged woman, two days apart in contiguous areas of the township. In doing extended fieldwork with Soweto Flying Squad, the author listened to the explanations and narratives that local people were constructing, both about the existence of otherwise unexplainable phenomena, and about the responses of neighbours, families, friends and enemies to the accusations made against particular people (most often women). In these narratives lie detailed accounts and understandings of the complex travails of rapid political and social change, underscored by the interwoven and often-contradictory expressions of multiple belief systems. Through an experience-near, highly contextualised ethnographic examination of several accusatory events from 1994 and 1995, the author explores the interlocking roles of narrative, gender and class, in processes of accusation in Soweto.